2015
DOI: 10.3386/w21079
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Conflict

Abstract: This research establishes that the emergence, prevalence, recurrence, and severity of intrastate conflicts in the modern era reflect the long shadow of prehistory. Exploiting variations across national populations, it demonstrates that genetic diversity, as determined predominantly during the exodus of humans from Africa tens of thousands of years ago, has contributed significantly to the frequency, incidence, and onset of both overall and ethnic civil conflict over the last half-century, accounting for a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…These measures take different forms: some account for distance between groups Ray 1994, 2011;Duclos, Esteban, and Ray 2004;Bossert, d'Ambrosio, and La Ferrara 2011;Esteban, Mayoral, and Ray 2012); others look at income inequality between ethnic groups (Huber and Mayoral 2013;Alesina, Michalopoulos, and Papaioannou 2016) or the historical depth of ethnic cleavages (Desmet, Ortuño-Ortín, and Wacziarg 2012); yet others consider heterogeneity between individuals rather than groups (Ashraf and Galor 2013a;Arbatli, Ashraf, and Galor 2015). Our paper is related to this literature because we propose new indices of heterogeneity both between and within ethnic groups.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…These measures take different forms: some account for distance between groups Ray 1994, 2011;Duclos, Esteban, and Ray 2004;Bossert, d'Ambrosio, and La Ferrara 2011;Esteban, Mayoral, and Ray 2012); others look at income inequality between ethnic groups (Huber and Mayoral 2013;Alesina, Michalopoulos, and Papaioannou 2016) or the historical depth of ethnic cleavages (Desmet, Ortuño-Ortín, and Wacziarg 2012); yet others consider heterogeneity between individuals rather than groups (Ashraf and Galor 2013a;Arbatli, Ashraf, and Galor 2015). Our paper is related to this literature because we propose new indices of heterogeneity both between and within ethnic groups.…”
mentioning
confidence: 92%
“…14 One possible explanation for the large share of within-group diversity is outlined in Arbatli, Ashraf, and Galor (2015): if initial diversity is positively associated with the formation of groups (Ashraf and Galor 2013b), yet there are scale effects implying a lower bound on the size of groups, then societies with particularly diverse traits will display both a high level of overall diversity while also displaying high within-group diversity. Such a mechanism could partly explain why total diversity is much larger than between-group diversity-both when considering genetic and cultural diversity.…”
Section: B the Overlap Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, as already mentioned, in our analysis we do not focus on the direct e¤ects of intergenerationally transmitted traits subject to selection, but on general measures of ancestry based on neutral genes, which tend to change randomly over time, and capture long-term relatedness across populations. Finally, our work is connected to a di¤erent but related set of contributions focusing on the economic and political e¤ects of genetic and cultural diversity not between populations, but within populations and societies Galor, 2013a, 2013b;Arbatli, Ashraf andGalor, 2013, Desmet, Ortuño-Ortín and. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Arbatli et al (2013) have argued that genetic diversity provides a "deeper" and better measure of diversity at the country level. Similarly, using cross-country data it has been shown that a sizable variation in income (Ashraf and Galor, 2013b), prevalence of civil conflict (Arbatli et al, 2013), mistrust and cultural fragmentation (Ashraf and Galor, 2013a) can be attributed to variations in genetic diversity.…”
Section: Introductionmentioning
confidence: 99%